Is Ireland the most intangible intensive economy in Europe? A growth accounting perspective - Ilias Kostarakos; Kieran McQuinn; Petros Varthalitis (The Economic and Social Research Institute (ESRI), 2022)
Assessing the contribution of intangible investment to growth is a challenging and complex task for any country. However, it has become increasingly difficult to determine both the exact magnitude of economic performance and its composition in the case of the Irish economy. This is mainly due to the impact of certain distortionary transactions by a select number of multinationals operating in the Irish jurisdiction. In this paper we address this issue by assessing, in a detailed manner, the contribution of intangible and tangible assets to the Irish growth story. We control for distortions in the official investment data series while also incorporating intangible assets which are not currently included in the National Accounts. Our results show that the observed unprecedented increase in the official intangible investment has a relatively minor contribution to the actual Irish labour productivity growth. Once the distortions are filtered out, Irish labour productivity growth is driven by tangible capital. More interestingly, non-national accounts intangible capital has a sizeable procyclical impact on labour productivity growth.
Keywords: 330; Wirtschaftswachstum; Arbeitsproduktivität; Betriebsvermögen; Immaterielle Werte; Irland